Pengaruh Excitement, Sophistication, dan Ruggedness terhadap Brand Trust melalui Brand Image sebagai Variabel Intervening pada Pengguna Tokopedia di Surabaya - Berlian Cinthya Devi; Nurul Azizah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine: (1) the effect of interest on the brand image of the Tokopedia site; (2) the influence of sophistication on the brand image of the Tokopedia site; (3) the effect of rudeness on the brand image of the Tokopedia site; (4) the influence of interest on the brand trust of the Tokopedia site; (5) the influence of sophistication on the brand trust of the Tokopedia site; (6) the effect of rudeness on the brand trust of the Tokopedia site; the population in this study, are users of the Tokopedia application who are domiciled in Surabaya. The number of samples in this study were 140 respondents. The sampling technique was purposive sampling with the criteria of consumers aged 17-30 years and had used the Tokopedia shopping site at least once in the Surabaya area. Data analysis technique using Partial Least Square with software smartPLS 3.0. The results of this study indicate that excitement, sophistication and toughness have a positive and significant influence on brand image. Meanwhile, excitement, sophistication and toughness have a positive but not significant effect on brand trust. indirectly excitement, sophistication and toughness have a positive and significant impact on brand trust through brand image. Keywords: Excitement, Sophistication, Ruggedness, Brand Image, Brand Trust